Issue Paper: Kentucky Omnibus Health Care Reform Act of 1986, Section 52 (Tufts Archival Research Center, 2007)
Issue paper on the Kentucky Omnibus Health Care Reform Act of 1986, Section 52. Defines legislation as requiring any group health insurance contracts in Kentucky to base premiums on tobacco use. Opposes legislation on the basis of its equity and its administrative ramifications. Questions research showing tobacco users have a higher incidence of morbidity/mortality. Accuses legislation of being unrealistic and unjustified.